PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KEPUASAN KERJA - Skolastika Dian Rosita Sari; Eko Agus Susilo; Harril Brimantyo (Jurnal Bisnis dan Manajemen, 2017)
This study aims  to determine the impact of and health on job satisfaction in Sugar Refinery Kebon Agung Malang. The number of population is 241 employees. The sampling technique using simple random sampling. Sample in this study using the Slovin formula, obtained the results as many  as 150 respondents. This study using descriptive analysis with quantitative approach using a questionnaire as a data collection tool and using the technique of multiple linear regression analysis to measure the influence of independent variables on the dependent variable is the salvation (X1) and health (X2) as the independent variable and job satisfaction as a variable dependent (Y). The results of this research stated  that safety and health has positive and significant impact to the job satisfaction in Sugar Refinery Kebon Agung Malang. This is shown by the value of Adjusted R Square of 0.427 or 4.27% by F significance 0,000 F and partial effect also show significant impact, this study found that health variables has a greater impact  influence on other vaiables, this is the show with a regression coeficient of 0.636 DOI : https://doi.org/10.26905/jbm.v4i2.1705